The Utilization of Medicine Plants by the Community of the Traditional Village Dasan Beleq Gumantar Regency, North Lombok, Indonesia - Hidayah, Nurul; Hadiprayitno, Gito; Karnan, Karnan; Irawan, Jono (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The traditional village community of Dusun Dasan Beleq is the oldest Sasak tribe in Lombok and still maintains local wisdom in using plants as traditional medicine. This study aimed to identify the plant species, parts, and processing methods used by the local community for medicinal plants. This type of research is descriptive. The data were collected through primary research, including semi-structured interviews and non-participatory observations. The respondents were selected by purposive sampling, including traditional leaders and the local community. The stages of data analysis are data reduction (Data Reduction), data presentation (Data Display), and conclusion. The results showed that the people of the Dusun Dasan Beleq Traditional Village had knowledge of 25 species from 22 plant families. Leaves are one of the most commonly used plant parts besides flowers, fruits, seeds, and rhizomes. The processing of medicinal plants used by the people of the Dusun Dasan Beleq Traditional Village involves methods such as pounding, boiling, and squeezing.